SATISFICING OPTION FOR BENEFIT COST ANALYSIS IN A HOUSING INFRASTRUCTURE PROJECT SELECTION - Farida Murti; Christiono Utomo (Simposium II UNIID 2017, 2017)
Decisions in large-scale housing project infrastructure planning are complex because they involve multiple parties such as planners, engineers, funders, and constructors. Many decisions during the development phase of the project such as routes and driveways and the location of construction materials. This paper presents a decision model that can be applied in the determination of alternative housing project development projects. The research used the process of satisficing option method where the benefits and cost for each alternative as a technical solution can be formulated on project evaluation. They are categorizing by the problem, comparing the benefits and costs, and representing the value of the project. Its scale is presented same. By creating Ps and Pr, the process can be done. Ps is a choice function that represents the project benefits and Pr is rejectability that represent project costs and normalize the problem. It makes the decision maker has a cost and benefit value to evaluate the proposed project. This method encourages future research for multi disciplines group decisions involving collaborative and negotiation processes